EVALUASI KINERJA APARATUR PEMERINTAH DESA MATANG DANAU DALAM MENINGKATKAN KUALITAS PELAYANAN PADA MASYARAKAT - Juang, Heru; Arma, Nur Ambia (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
The aim of this research is to determine the Performance Evaluation of Matang Danau Village Government Apparatus in Improving the Quality of Service to the Community. This study uses a qualitative method. The informants in this research were the Chairman of the BPD, Village Head, Village Secretary, and 3 (three) community leaders. This research uses qualitative data analysis where existing data obtained from observations, interviews and documentation are analyzed using descriptive methods using inductive thinking. The results of this research show that the performance of the Matang Danau Village government apparatus has not been running well. The work commitment of the Matang Danau Village officials in their work is still low, this means that the discipline of the officials in implementing the principles of public service does not work well. The Matang Danau Village government's punctuality in working is also not optimal. The comfort of Matang Danau Village government services is also not optimal. Although the quality of service provided by the Matang Danau Village government is quite good. Apart from that, the effective use of technology and resources is also carried out quite well by the Matang Danau Village government. The government of Matang Danau Village has also responded quickly to community problems.